Presence of reproductive haplotypes and their effect on a dairy cattle population in the central coast of Peru - Calderón Velásquez, Jorge Pedro (2021)
Reproductive records (n=6350) of a dairy herd between 2000 and the first semester of 2016 were used based on the reproductive indices of the herd, considering the number of services per pregnancy, open days, pregnancy rate and occurrence of abortions. In total, 58 Holstein cows selected at random were genotyped to determine the presence of reproductive haplotypes (HH) that affect the reproductive performance of cows causing abortions. It was determined that 5.2% of the cows were carriers for HH1, 5.2% for HH3 and 3.4% for HH5, not finding carrier animals for the HH2 and HH4 haplotypes. Besides, 75% of the carrier cows (6/8) presented abortions not associated with the haplotype, except for one event whose reproducer was a carrier for HH3. Likewise, 54% of the non-carrier cows presented abortion events (27/50), not establishing a direct effect of the haplotype on the occurrence of abortions. The number of services per pregnancy associated with the genomic conception rate (CCR) determined a correlation of 8.3% (p>0.05) and a regression coefficient of -0.07115 services (p>0.05). Of the five genetic groups of sire parenthood found in the herd, four genetic groups are present through the progeny of males that presented the reproductive haplotypes.